New records of the family Hydroptilidae for the caddisfly (Insecta: Trichoptera) fauna of Slovenia - Gorazd Urbanič (Natura Sloveniae)
A list of fourteen new Hydroptilidae records for the Slovenian caddisfly fauna is given. Genera Agraylea and Stactobia were recorded for the first time in Slovenia. Hydroptila rheni Ris 1903 has been previously known only from a type locality in Switzerland. The number of recorded Slovenian caddisfly species has thus increased to 238.